2020
DOI: 10.4236/asm.2020.102003
|View full text |Cite
|
Sign up to set email alerts
|

Do False Beliefs Predict Increased Circumcision Satisfaction in Men?

Abstract: Medical male circumcision has been adopted by the WHO, and other professional public health and medical bodies, as a vital weapon in the fight against HIV. This has prompted a large body of research into the acceptability of the procedure, attitudes to it, and barriers to it. A systematic review of these studies found that satisfaction with circumcision is strongly associated with having accurate knowledge about it. A survey-based paper by Earp, Sardi and Jellison entitled "False beliefs predict increased circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Curiously, instead of accepting the ndings at face value, the authors suggested that circumcised men held false beliefs by refusing to accept that they had been harmed by their NMC. Multiple aws in the study were identi ed [213].…”
Section: Sexual Healthmentioning
confidence: 99%
“…Curiously, instead of accepting the ndings at face value, the authors suggested that circumcised men held false beliefs by refusing to accept that they had been harmed by their NMC. Multiple aws in the study were identi ed [213].…”
Section: Sexual Healthmentioning
confidence: 99%
“…Thus, men with normal sexual function who believe the fallacies may think that their sex life has been diminished by their NMC, causing anxiety and resentment of their parents’ decision to have them circumcised 93 . Over 40 studies have shown consistently that the more well‐informed men are about MC the more positive they are about it 94 . We contend that it is misinformation that breeds negative psychological consequences, not MC itself.…”
Section: Discussionmentioning
confidence: 86%
“…93 Over 40 studies have shown consistently that the more well-informed men are about MC the more positive they are about it. 94 We contend that it is misinformation that breeds negative psychological consequences, not MC itself.…”
Section: Societal Influencesmentioning
confidence: 99%
“… 113 But instead of accepting the findings as had been reported by the men, Earp et al suggested that the men had adopted “ false beliefs ” to “‘ justify ’ their genitally altered state .” In a critique, Moreton pointed out serious flaws in the study, including that (i) half of the 10 “true/false” statements used in the survey were questionable, (ii) all of the extensive literature contradicting the findings was ignored, and (iii) the pivotal issue regarding whether dissatisfied circumcised men have false beliefs concerning MC was ignored. 114 Moreton concluded that because of the serious flaws he identified, readers should dismiss the study as misleading.…”
Section: Studies Claiming Adverse Effects On Sexual Function Sensitimentioning
confidence: 99%